Factors associated with knowledge and practice of breast self-examination among female governmental school teachers in Gondar Town, Northwest Ethiopia, 2019 - Yazew, Birhaneslasie Gebeyehu; Alemu, Biresaw Wassihun; Walle, Tarkie Abebe (Frontiers in Oncology, 2024)
BackgroundBreast cancer is the most common cancer among women globally, and early detection through breast self-examination can improve survival rates. However, this practice is limited in developing countries like Ethiopia.ObjectiveThis study aimed to assess the factors influencing knowledge and practices related to breast self-examination among female governmental school teachers in Gondar Town, Northwest Ethiopia.MethodsA cross-sectional study was conducted from May 1 to 30, 2019, with 422 female teachers in Gondar metropolis governmental schools selected through simple random sampling. Data were collected using a self-administered questionnaire and analyzed using EPI INFO version 7 and SPSS version 20.ResultA total of 415 female teachers participated in the study, with a response rate of 98.3%. The mean age of respondents was 38.64 years. Only 41.9% had good knowledge of breast self-examination, while 14.5% reported good practice. Factors associated with knowledge included secondary education, higher degrees, and exposure to information. Factors influencing practice included having a degree or higher education and prior experience with breast self-examination.Conclusion and recommendationThe study revealed low levels of knowledge and practice of breast self-examination among female teachers. Educational level was significantly associated with both knowledge and practice. Recommendations include implementing health education campaigns, organizing events like breast cancer awareness days, and forming support groups in schools to promote awareness and encourage regular breast self-examination among female teachers in Ethiopia.